The effects of top pruning on growth and production of conelets and cones in Pinus brutia Ten seed orchards of different ages - Alan, Murat (Array, 2018)
In economic and biological terms (rapid growth, the ability to produce seeds at an early age, etc.) Pinus brutia Ten. is one the most important forest tree species in Turkey. Considerable progress has been made in Pinus brutia Ten. breeding program and both phenotypical and according to the results of progeny trials, totaling 615-hectare seed orchardshas been established. Pinus brutia Ten. seed orchardshas reached 43% of the total orchard area and covered the largest area.To acquire information on the management of seed orchards, top pruning has been carried out on three Pinus brutia Ten. seed orchards of different ages (old, middle-aged and young). Two top pruning regimes were applied in these three seed orchards, once in 2008 to the old orchard, while a single topping regime was applied in 2008 and 2012 to the middle-aged and young orchards.Each year, the height, diameter at breast height, and bi-directional crown diameter were measured, and all conelets and cones on ramets were counted beforeand after pruning.At the end of four years, control ramets in old and young seed orchards had higher values of height, diameter at breast height, and volume indexcompared to the middle-aged orchard. On the other hand, even though the control ramets in the middle-aged seed orchard reached a greater height, pruned ramets reached a greater volume index and diameter at breast height. While the height differences observed between control and pruned ramets in all seed orchards at the beginning eventually decreased, it was observed that the heights of pruned ramets grew proportionally larger.No difference was founded between the control and pruned ramets in terms of cone and conelet production. Pruning intervals and regimes varied in old, middle-aged and young seed orchards, and it was acknowledgedthat top pruning could be used for old, middle-aged and young seed orchard managements.